Control System Design for 3 Storey Elevator Using PLC OPTA FINDER - Suparmono; Sitepu, Trahman; Salman, Aulia; Pardede, Sutan; Cholish; Abdullah; Nofri, Irfan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Elevators are a crucial vertical transportation system in multi-story buildings, and the use of an appropriate control system can enhance operational efficiency, comfort, and safety. This study aims to design a control system for a 3-floor elevator using a Programmable Logic Controller (PLC) OPTA FINDER, which offers advantages in flexibility and ease of programming. The design process involved creating a control system schematic, programming with ladder diagrams, and testing on a small-scale elevator model. The test results demonstrated that the system could operate the elevator with fast and accurate response in detecting floor positions, controlling automatic doors, and responding to emergency conditions. Furthermore, the PLC OPTA FINDER proved reliable in managing elevator system components and facilitating program modifications without requiring hardware changes. This control system also contributes to energy efficiency through optimized motor speed regulation. Thus, the implementation of the PLC OPTA FINDER provides an effective and safe solution for modern elevator control systems.